IMPLANTAÇÃO DE ALOJAMENTO CONJUNTO MÃE-BEBÊ EM UNIDADE PSIQUIÁTRICA - Artmann, Marcelo (2021)
This study was outlined with the aim of collaborating with actions for qualify humanization in the care at a psychiatric hospitalization unit, especially through an environment that promotes mother-baby living. This dissertation focuses on the implementation of a joint accommodation in a psychiatric unit, in view of the concern with the maintenance/strengthening of the bond between mother and child in the hospital setting. The high rate of mental disorders in pregnant women and mothers of babies, in Brazil, denotes the importance of creating an environment that allows the coexistence of the mother and baby during psychiatric hospitalization, favoring bonding and breastfeeding in the first 12 months of the child’s life. In addition, the importance of conducting such a study in Brazil is emphasized, because it is an unprecedented experience in the country. Objective: To implement a joint housing (Mother Baby Unit) in a psychiatric unit of a university hospital located in the central region of Rio Grande do Sul. Methodological itinerary: Initially a review of the international literature was performed. Afterwards, the collection of data from a qualitative research was started in the period from April to December 2020, in the psychiatric unit. Twenty-eight professionals from the multiprofessional health team participated, using an instrument with closed and open questions. Results: The international literature presents promising results for mother and baby, in the modality of joint hospitalization. The multiprofessional team, participating in this study, was favorable to the experience in the unit, as they understood the joint accommodation as a therapeutic tool in the treatment of the patients with children in the first months of life. The team showed that the strengthening of the mother-baby bond can contribute positively to the patient’s treatment. Final considerations: The results of the research served as a foundation for the adequacy of the physical environment/infrastructure of the unit. Thus, the joint accommodation in the unit was created, which aims at not separating the mother from the baby, allowing the follow-up of breastfeeding and the exercise of motherhood, favoring the mother-baby relationship and the health of both. The welcoming space, built on the principles of humanization of the Serviço Público de Saúde – SUS, will also contribute to the reduction of the necessary time of hospitalization and recurrences, already described in international experiences. Product: It's about a social technology, a humanized hospital space to function as joint accommodation mother-baby in psychiatric unit. For this, a suite with bathroom for individual admission of the pregnant woman or mother was adapted. The space was renovated and suitable for the comfort of the mother and baby, according to suggestions from the multiprofessional team such as: cot, breastfeeding chair, chest of drawers, bathtub, diaper changer, among others. The product was finalized and is already available to the team, it is being used, according to the demand for hospitalization of mothers, in the unit.